2019
DOI: 10.1186/s12888-019-2375-1
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal trajectories of comorbid PTSD and depression symptoms among U.S. service members and veterans

Abstract: BackgroundPosttraumatic stress disorder (PTSD) often co-occurs with other psychiatric disorders, particularly major depressive disorder (MDD). The current study examined longitudinal trajectories of PTSD and MDD symptoms among service members and veterans with comorbid PTSD/MDD.MethodsEligible participants (n = 1704) for the Millennium Cohort Study included those who screened positive at baseline for both PTSD (PTSD Checklist–Civilian Version) and MDD (Patient Health Questionnaire). Between 2001 and 2016, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 62 publications
5
60
0
1
Order By: Relevance
“…First and foremost, the results indicated that the longitudinal course of depression was heterogeneous, which is consistent with previous studies that found significant interindividual variety in long-term posttraumatic reactions, such as PTSD (e.g., Bonanno et al, 2010) and depression (Armenta et al, 2019;Bonanno et al, 2012;Sampson et al, 2015). The largest trajectory group was the resilient group, a result which is consistent with previous studies on the course of depression with traumatized populations that did not participate in war (e.g., Bonanno et al, 2012;Maccallum et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…First and foremost, the results indicated that the longitudinal course of depression was heterogeneous, which is consistent with previous studies that found significant interindividual variety in long-term posttraumatic reactions, such as PTSD (e.g., Bonanno et al, 2010) and depression (Armenta et al, 2019;Bonanno et al, 2012;Sampson et al, 2015). The largest trajectory group was the resilient group, a result which is consistent with previous studies on the course of depression with traumatized populations that did not participate in war (e.g., Bonanno et al, 2012;Maccallum et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…"recovery," high depression at baseline and gradually declining symptoms; and "delayed," initially none or minimal depression symptoms followed by an elevation (e.g., Bonanno et al, 2012;Maccallum et al, 2015;Nandi et al, 2009). However, these studies have typically investigated the years immediately after the traumatic experience and covered relatively short time periods of up to 6 years, with the exception of Armenta et al (2019) who followed veterans suffering from both PTSD and depression for 15 years after the war and found four distinct trajectories of depression (chronic, relapse, gradual recovery, and rapid recovery). To the best of our knowledge, no studies to date have examined distinct latent trajectories of depression among veterans, decades after the trauma and over extended periods of time.…”
Section: Depression As An Outcome Of Combat and Captivitymentioning
confidence: 99%
“…Given the broad range of factors linked to insomnia (Killgore et al, 2020 ; Mandelkorn et al, 2021 ; Yuksel et al, 2021 ), we explored how a comprehensive array of pre‐ and peri‐pandemic risk and protective factors related to new‐onset and exacerbated insomnia symptoms. In addition, given the high prevalence of posttraumatic stress disorder (PTSD) and major depressive disorder (MDD) in veterans (Armenta et al, 2019 ), as well as a strong association between these disorders and insomnia (Britton, McKinney, Bishop, Pigeon, & Hirsch, 2019 ), we additionally considered how these pre‐existing psychiatric morbidities might influence pandemic‐related changes in insomnia symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Post-traumatic stress disorder (PTSD) is a prevalent, debilitating disorder that develops in a subset of individuals following exposure to trauma. PTSD is highly comorbid with depressive as well as other mental health disorders [1][2][3] . Indeed, epidemiological estimates suggest that >50% of individuals with PTSD also have a major depressive disorder (MDD) diagnosis [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%